Social Media Education for the ASEAN Digital Generation: Strengthening Identity and Global Responsibility - Enjang Pera Irawan; Dhani Irmawan; Muhammad Raqib Bin Mohd Sofian (PT Inovasi Pratama Internasional, 2026)
The rapid development of digital technology has transformed the way younger generations build their identities, interact socially, and engage in global communication. In Indonesia, the high use of the internet and social media among adolescents has not been accompanied by adequate competencies in digital ethics, critical literacy, and online safety. The National Digital Literacy Index indicates that Indonesia’s digital literacy remains at a moderate level, particularly in the areas of digital ethics and digital safety. In addition, adolescents are vulnerable to misinformation and digital manipulation, highlighting the need for educational interventions based on ethics and digital responsibility. This Community Service Program aims to improve digital literacy and ethical social media practices among students of SMK 47 Jakarta Selatan through collaboration with Universiti Sains Islam Malaysia. The program was implemented through workshops, interactive discussions, and pre-test and post-test evaluations. The results showed improvements in students’ understanding of digital ethics, information verification, responsible social media behavior, and digital safety. The program also strengthened institutional collaboration at the ASEAN level and produced an ethics-based digital literacy educational module for vocational school students